Factors Affecting the Smart Port Implementation at Laem Chabang Deep Sea Port, Thailand - Kanokporn Nakchatree; Jaruwit Prabnasak (My University, 2023)
This study aims at developing and validating a model of causal factors potentially affecting long-term development of Laem Chabang Deep-Sea Port in Thailand. The data collected by a questionnaire survey has been analyzed by a measurement model of latent variables. Several key hypotheses have also been tested by the proposed model. According to the model analysis, it is found that the empirical data analysis is consistent with the theoretical measurement model. The prosperous development is positively influenced with statistical significance by four latent variables – as represented by the following statistics: CMIN/P = 0.068, CMIN/df = 1.282, GFI = 0.976, and RMSEA = 0.027. Additionally, results from the Second Confirmatory Factor Analysis (SCFA) shows that there are two factors considered as key success factors for smart port implementation at the port. It is found that all four factors are rated at high-level of importance with operation, environment, safety and security, and energy, respectively.
Keywords: Port (circuit theory); Maritime Ports and Logistics